2022
DOI: 10.3758/s13415-022-01012-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for lateralized functional connectivity patterns at rest related to the tendency of externalizing or internalizing anger

Abstract: Previous electroencephalographic and brain stimulation studies have shown that anger responses may be differently lateralized in the prefrontal cortex, with outward-oriented responses (externalized anger) linked to left prefrontal activity, and inward-oriented responses (internalized anger) linked to right prefrontal activity. However, the specific neural structures involved in this asymmetry, and how they interact to produce individual differences, remain unexplored. Furthermore, it is unclear whether such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
0
3
1
Order By: Relevance
“…The involvement in the anterior cingulate in rumination and internalization of anger may appear contradictory to our findings, which show a positive association between the cingulate and externalization. However, in our study, the cingulate area was more centrally located and posterior compared to the anterior cingulate observed in previous studies on rumination and internalization (Denson et al 2009; Consolini et al 2022).…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…The involvement in the anterior cingulate in rumination and internalization of anger may appear contradictory to our findings, which show a positive association between the cingulate and externalization. However, in our study, the cingulate area was more centrally located and posterior compared to the anterior cingulate observed in previous studies on rumination and internalization (Denson et al 2009; Consolini et al 2022).…”
Section: Discussioncontrasting
confidence: 63%
“…Another important region in our study was the Cingulate cortex. The cingulate, especially the anterior part, as well as the medial prefrontal area, have been associated to angry rumination (Denson et al 2009), which characterizes the internalization of anger (Consolini et al 2022). Indeed, in one study, authors found that after the presentation of angry faces, the negative connectivity of the ventral anterior cingulate cortex with the amygdala was reduced in individuals with high appetitive motivation (associated with aggression) (Passamonti et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations